Rice Price and Climate Change: A Panel Study in Indonesia - Alghiffary, Muhammad Achyar Izzulislam; Perwithosuci, Winny (Universitas Muhammadiyah Surakarta, 2024)
Purpose: Rice is the staple food for most Indonesians. The increasing population will lead to a higher demand for rice and its price. The higher price becomes an issue since rice is one of the staple foods. If the rice price remains high, only a few groups of people can afford it. Meanwhile, demand is not the only factor that increases the price of the rice. Climate change can also affect rice prices through rainfall changes that lead to changes in harvest season. That condition will decrease the rice supply and increase the rice price. Thus, this study aims to examine the factors that affect the rice price in 33 provinces in Indonesia. Methodology: This study utilizes secondary data from Statistics Indonesia from 2018 to 2023. This study treats rice prices as the dependent variable. The independent variables consist of rice production, agricultural labour absorption, rainfall as the proxy of climate change, and per capita income. Results: The study revealed that rice production has a positive impact on rice prices, labour has a negative impact on rice prices, rainfall has a negative impact on rice prices, and income per capita has a positive impact on rice prices. Applications/Originality/Value: This study's results surely add to the gap regarding the determinant of rice price investigated by using climate change issues. The results revealed that there is an effect of rainfall as the proxy of climate change on rice prices in Indonesia. The findings imply that climate change mitigation and adaptation should be conducted in the agricultural sector to maintain the stability of rice prices.